Judicialização da política de saúde e sua correlação com o planejamento em saúde do município de Cuiabá/MT - Santos, Silvana Barboza dos (2023)
The promulgation of health as a right for all and a duty of the State in the Federal Constitution brought significant gains to the Brazilian population, mainly due to its universal, comprehensive and free public nature. However, the implementation of this offer to citizens has faced obstacles since its conception, which was permeated by capitalist influences and interests. With the advancement of technology and the private market to the detriment of public services, problems related to health have taken on significant dimensions as the available supply of services in the Unified Health System does not cover the dimension foreseen in the constitutional text. This mismatch leads to conflicts between the citizen and the executive power, resulting in the judicialization of health, which, in this research, is limited exclusively to the scope of public health. In this sense, this dissertation aims to present an investigation into the correlation between judicialization and the planning process in the Health Policy in Cuiabá/MT from 2017 to 2020, in order to understand the impacts on the health services offered. The research has a social and not a legal character, therefore, its theoretical bases are authors who debate the complexity and duality of this phenomenon that has gained ground in the judiciary, with repercussions on the executive. For this discussion, we use dialectical historical materialism as a methodology for the analysis of social phenomena constituted by capitalist society, with a qualitative approach. It is an exploratory and documentary research that used bibliographic review techniques in books and scientific articles in the field of Social Service, Public Health, health law and political economy, also using data collected from the Municipal Health Department of Cuiabá. The research demonstrated a significant increase in judicialization at a national level and an oscillation of the phenomenon in the municipality of Cuiabá. A likely cause is disorganization regarding the systematization of information, therefore bringing important consequences to the planning process. Ignorance of the phenomenon hinders the development of effective policies that could culminate in the reduction of judicialization. This process has a strong social and economic character, restricting access to audiences with a higher level of education and greater purchasing power, and is therefore selective. It thus demonstrates that it is not the best way to access healthcare, and is even a means of generating disorder in the provision of public services. However, it was possible to observe that there are interests in this “disorganization”, and in the effective increase in judicialization, to the extent that it benefits large companies, and superimposes individual rights to the detriment of the collective, in an evident appropriation of public funds.